2018
DOI: 10.1038/s41395-018-0421-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact and Safety of Anticoagulants for Portal Vein Thrombosis in Cirrhosis

Abstract: Objectives: Portal vein thrombosis (PVT) is a frequent complication of cirrhosis. Benefit, safety, and duration of anticoagulant treatment in this setting are controversial issues. The aim of this study was to analyze the course of PVT in a large cohort of cirrhotic patients undergoing or not anticoagulation therapy. Methods: The data of 182 patients who presented between January 2008 and March 2016 with cirrhosis and PVT with at least 3 months of follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
116
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 119 publications
(130 citation statements)
references
References 26 publications
12
116
2
Order By: Relevance
“…34 Finally, an increasing number of studies have evaluated the most important issue, which is the impact of recanalization on survival and the need for liver transplantation. None of these studies except one 28 found any influence, 29,30,32,35,64,67 although univariate analyses often suggested that recanalization was favourable. On the other hand, several studies have suggested that anticoagulation therapy has an independently positive effect, regardless of recanalization or the severity of liver disease.…”
Section: In Patients With Cirrhosismentioning
confidence: 98%
See 4 more Smart Citations
“…34 Finally, an increasing number of studies have evaluated the most important issue, which is the impact of recanalization on survival and the need for liver transplantation. None of these studies except one 28 found any influence, 29,30,32,35,64,67 although univariate analyses often suggested that recanalization was favourable. On the other hand, several studies have suggested that anticoagulation therapy has an independently positive effect, regardless of recanalization or the severity of liver disease.…”
Section: In Patients With Cirrhosismentioning
confidence: 98%
“…Results on analyses to identify predictors for recanalization on anticoagulation therapy have been varied. The delay in initiating anticoagulation is the only consistent factor …”
Section: Portal Vein Thrombosis In Patients With Cirrhosismentioning
confidence: 99%
See 3 more Smart Citations